A Guide to Panini : An English Summary of Panini's Aphorisms on Sanskrit Grammar - Vancatavaradiengar, S. (Brill | Manohar Publishers & Distributors, 2024)
Panini, who lived between the sixth and fourth century BCE, was one of the few ancient grammarians, whose works are widely taught in the field of linguistics. Divided into six parts, the book is a useful manual to study ancient Sanskrit grammar devised by Panini. The book covers teaching the art of alphabets, the sandhi rule, verbs, nouns, noun roots, and syntax rules. Overall, this book is a summary of Panini's dictum on Sanskrit grammar. This book is written in both Kannada and English in explaining the ancient Sanskrit grammar rules.